2005
DOI: 10.1139/f05-003
|View full text |Cite
|
Sign up to set email alerts
|

Divergent impacts of experimental lake-level drawdown on planktonic and benthic plant communities in a boreal forest lake

Abstract: Water-surface elevation in lake 226 (L226) of the Experimental Lakes Area in northwestern Ontario, Canada, was lowered experimentally by 2–3 m during each of three successive winters, and increased naturally but incompletely during the ensuing summers. Our objective was to compare the responses of the littoral and pelagic plant communities to this physical disturbance. Water-chemistry changes were muted, and neither nitrogen nor phosphorus concentration changed. Phytoplankton biomass, species assemblages, prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 12 publications
3
56
0
Order By: Relevance
“…Two studies on contemporary lake-level change give insight into mechanisms behind such diversity changes. Turner et al (2005) investigated the effect of lake drawdown on algal communities, and reported macrophyte diversity and cover decline with the loss of emergent vegetation and increased percentage of barren substrate as littoral area declined. An initial decrease in diatom diversity occurred following drawdown.…”
Section: Diversitymentioning
confidence: 99%
“…Two studies on contemporary lake-level change give insight into mechanisms behind such diversity changes. Turner et al (2005) investigated the effect of lake drawdown on algal communities, and reported macrophyte diversity and cover decline with the loss of emergent vegetation and increased percentage of barren substrate as littoral area declined. An initial decrease in diatom diversity occurred following drawdown.…”
Section: Diversitymentioning
confidence: 99%
“…Few studies have examined the effect of winter drawdowns on changes of element and ion concentrations in water (Turner et al 2005) and sediments (Peverly and Kopka 1991). Increases in calcium concentration is evident upon re-wetted conditions, as seen in soft-water lakes (Peverly and Kopka 1991;Turner et al 2005).…”
Section: Nutrient Dynamicsmentioning
confidence: 99%
“…As turbidity and Chl-a increased, food items for calanoids could have decreased while those for cyclopoids increased; alternatively, calanoids may have had difficulty detecting their food items as a result of the increased turbidity (Strickler 1982;Andrews 1983;Arruda et al 1983;Price et al 1983;DeMott 1986;Legier-Visser et al 1986;Van Alstyne 1986). It is also possible that changes in zooplankton abundance and assemblage composition were a consequence of changes in predation by a larval fish assemblage that was dissimilar between pre-drawdown and post-drawdown (sensu Martin et al 1981;Turner et al 2005;Olds et al 2014).…”
Section: Zooplankton Assemblagementioning
confidence: 99%
“…This could have resulted from many factors, including an increase in zooplankton production (i.e., greater abundance of younger [smaller] individuals), changes in predation patterns, and lack of refugia (Turner et al 2005). However, because we only identified Bosmina and Daphnia to genus, and copepod nauplii to subclass, it is possible that the observed changes in size were merely changes in abundances of taxa below the taxonomic level to which we identified zooplankters.…”
Section: Zooplankton Assemblagementioning
confidence: 99%